Mirror-Integrated Transparent Antenna for RFID Application - Serra, C. C.; Medeiros, C. R.; Costa, J. R.; Fernandes, C. A. (IEEE Antennas and Wireless Propagation Letters, 2011)
An optically transparent antenna array is presented for radio frequency identification (RFID) systems, operating in the ultrahigh frequency (UHF) band. The antenna is intended for non-intrusive integration into the mirror surface of fitting rooms in apparel stores, keeping with the typical small depth of the mirror structure and low cost. The antenna is used to read RFID tags attached to clothes being tried on, so that the associated system can automatically provide the client with interactive information regarding that specific piece of clothing. The antenna ensures self-confined reading range in front of the mirror, avoiding undesired detection of RFID tags from adjacent fitting rooms. The final antenna solution shows a good compromise between transparency and performance, with well-confined RFID detection volume.